Cellular immunotherapy in multiple myeloma - Vo, Manh-Cuong; Lakshmi, Thangaraj Jaya; Jung, Sung-Hoon; Cho, Duck; Park, Hye-Seong; Chu, Tan-Huy; Lee, Hyun-Ju; Kim, Hyeoung-Joon; Kim, Sang-Ki; Lee, Je-Jung (The Korean journal of internal medicine, 2019)
In multiple myeloma (MM), the impaired function of several types of immune cells favors the tumor's escape from immune surveillance and, therefore, its growth and survival. Tremendous improvements have been made in the treatment of MM over the past decade but cellular immunotherapy using dendritic cells, natural killer cells, and genetically engineered T-cells represent a new therapeutic era. The application of these treatments is growing rapidly, based on their capacity to eradicate MM. In this review, we summarize recent progress in cellular immunotherapy for MM and its future prospects.